Determining the Minimarket Sales Pattern with the Apriori Algorithm Association Data Mining Method - Dewi Kartika; Kusnawi Kusnawi (STMIK Banjarbaru, 2023)
By reviewing the various needs of the community in areas that are not covered by national minimarkets, Gemilang minimarket has become one of the providers of a variety of supporting products to the basic needs of residents around the supermarket area. The limitations of the transaction technology used are considered to be prone to causing losses to company management. Renewable data management using algorithms and digital media will build better transaction and organizational patterns. This study applies the Apriori algorithm to determine frequent item sets. The Apriori algorithm is the process of using data mining methods to describe findings related to databases, as well as the application of association analysis techniques to determine item combination rules to improve methods in designing minimarket applications. Thus, business owners can control inventory, sales percentage, and design strategies to minimize losses. The results of the design carried out create a website-based application that can be tailored to user needs, so that it is hoped that it can create innovative strategies to support Minimarket business development.Keywords: Data Mining; Apriori Algorithm; Association Rule AbstrakDengan meninjau beragam kebutuhan masyarakat pada daerah yang tidak terjangkau oleh minimarket nasional, menjadikan minimarket Gemilang menjadi salah satu penyedia beragam produk penunjang hingga kebutuhan pokok warga di sekitar area supermarket. Keterbatasan teknologi transaksi yang digunakan dinilai rawan menimbulkan kerugian bagi manajemen perusahaan. Pengelolaan data yang terbarukan menggunakan algoritme serta media digital, akan membangun pola transaksi dan pengorganisasian dengan lebih baik. Penelitian ini menerapkan algoritme Apriori untuk menentukan frequent item set. Algoritme Apriori merupakan proses penggunaan metode data mining untuk penggambaran terkait penemuan pada database, serta penerapan teknik analisis asosiasi untuk menentukan aturan kombinasi item guna menyempurnakan metode dalam perancangan aplikasi minimarket. Dengan demikian, pemilik usaha dapat mengontrol persediaan, presentase penjualan, hingga merancang strategi guna meminimalkan kerugian. Hasil perancangan yang dilakukan menciptakan sebuah aplikasi berbasis website yang dapat disesuaikan dengan kebutuhan pengguna, sehingga diharapkan dapat menciptakan strategi yang inovatif sebagai penunjang perkembangan bisnis Minimarket.